2017
DOI: 10.1016/j.ijrobp.2016.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Local Control From Consolidative Radiation Therapy in High-Risk Neuroblastoma Despite Gross Residual Disease, Positive Margins, or Nodal Involvement

Abstract: Purpose To report the influence of radiation therapy (RT) dose and surgical pathology variables on disease control and overall survival (OS) in patients treated for high-risk neuroblastoma at a single institution. Methods and Materials We conducted a retrospective study of 67 high-risk neuroblastoma patients who received RT as part of definitive management from January 2003 until May 2014. Results At a median follow-up of 4.5years, 26patients (38.8%) failed distantly; 4 of these patients also failed locall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
3
14
0
Order By: Relevance
“…Our study adds to the scant proton literature and is consistent with the existing proton and photon literature with longer follow-up. [1][2][3][4]8,10 The predominant site of failure is progression in post-induction non-MIBG-avid distant sites, similar to previously published reports. 3,11,12 Although proton therapy provides high rates of local control with acceptable toxicity for neuroblastoma, our results suggest that advances in systemic therapy are needed for improved control of systemic disease.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our study adds to the scant proton literature and is consistent with the existing proton and photon literature with longer follow-up. [1][2][3][4]8,10 The predominant site of failure is progression in post-induction non-MIBG-avid distant sites, similar to previously published reports. 3,11,12 Although proton therapy provides high rates of local control with acceptable toxicity for neuroblastoma, our results suggest that advances in systemic therapy are needed for improved control of systemic disease.…”
Section: Discussionsupporting
confidence: 89%
“…We did not exclude any patients with local failures occurring within 12 months. Our study adds to the scant proton literature and is consistent with the existing proton and photon literature with longer follow‐up . The predominant site of failure is progression in post‐induction non‐MIBG‐avid distant sites, similar to previously published reports .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…[ 31 ] Studies have demonstrated that patients with low risk disease can be treated with surgery alone and supported a role for >90% resection of the primary tumor in high-risk patients. [ 32 ] Although overall survival is excellent for patients who have low- and intermediate-risk neuroblastoma with a general trend toward minimization of therapy, mortality rate is still high for high-risk patients. [ 33 ] Thus it is of importance to identify the characteristics which could predict the outcomes of patients.…”
Section: Discussionmentioning
confidence: 99%